Kegiatan Pengabdian Masyarakat Pemetaan Status Gizi Siswa-Siswi Di Sekolah Dasar Negeri 02 Ciherang Sebagai Langkah Awal Cegah Masalah Gizi - Alexander Halim Santoso; Junius Kurniawan; Farell Christian Gunaidi; Khalisya Alifia; Clarissa Hartawan; Chandy Linardi; Corry Calista (Jurnal Pengabdian Masyarakat, 2024)
Nutritional intake is essential for human survival, health, and cognitive development at every stage of life. South Asia is home to adolescents who are significantly affected by stunting, waste, and overweight, with respective rates of 13.0%, 10.8%, and 10.8%. This service activity is intended to compile a nutritional status map of the students attending SDN Ciherang 01. The design of this activity was conducted utilizing the Plan-Do-Check-Act (PDCA) methodology. 125 students participated in this activity, during which anthropometric assessments were conducted to determine the nutritional status of the students: body weight, height, and body mass index were measured. As per the findings of this service, 9.6% of students exhibited overweight status, 12.8% demonstrated obesity, and 18.4% reported being underweight. Immediate action is required to avert the adverse effects that identified nutritional issues may have on the growth and development of students.